Approaches to Facilitate Improved Recruitment, Development, and Retention of the Rural and Remote Medical Workforce: A Scoping Review Protocol - Farah Noya; Kirsty Freeman; Sandra Carr; Sandra Thompson; Rhonda Clifford; Denese Playford (International Journal of Health Policy and Management, 2021)
Background Medical workforce scarcity in rural and remote communities is a global problem, severely challenging healthcare delivery and health equity. Both developed and developing countries report geographically uneven distributions of the medical workforce. This scoping review synthesizes evidence from peer-reviewed and grey literature concerning approaches implemented to improve the recruitment, development, and retention of the rural medical workforce in both developed and developing countries.   Methods We will utilize the Arksey and O’Malley (2005) framework as the basis for this scoping review. The databases to be searched include Medline, Embase, Global Health, CINAHL Plus, and PubMed for articles from the last decade (2010-2019). Searches for unpublished studies and grey literature will be undertaken using the Google Scholar - Advanced Search tool. Quantitative and qualitative study designs will be included. Two authors will independently screen and extract relevant articles and information, with disagreements resolved by a third. Quantitative and qualitative analyses (thematic) will be conducted to evaluate and categorize the study findings.   Discussion The scoping review will aid in mapping the available evidence for approaches implemented to advance the process of recruitment, development, and retention of the medical workforce in the rural and remote areas in developed and developing nations.   Registry This protocol has been registered to Open Source Framework (https://osf.io/e83hp/).